Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Suppose that $X_1, X_2, ..., X_n$ and $Y_1, Y_2, ..., Y_n$ are independent random samples from populations with means $\mu_1$ and $\mu_2$ and variances $\sigma_1^2$ and $\sigma_2^2$, respectively. Show that the random variable

$U_n = \frac{(\bar{X} - \bar{Y}) - (\mu_1 - \mu_2)}{\sqrt{\frac{(\sigma_1^2+\sigma_2^2)}{n}} }$

satisfies the following conditions of the theorem below and thus that the distribution function of $U_n$ converges to a standard normal distribution function as $n -> \infty$.

Theorem:enter image description here

I'm not exactly sure how to exactly approach this but I was told to consider $W_i = X_i - Y_i$, for $i = 1, 2, ..., n$.]

share|improve this question
    
A first step would be to determine the mean and variance of $W_i$. –  user133281 Mar 5 at 20:30

1 Answer 1

up vote 4 down vote accepted

Let $W_i=X_i-Y_i$, then $\mu_W=E[W_i]=E[X_i-Y_i]=E[X_i]-E[Y_i]=\mu_1-\mu_2$,

Also, you can show that the variance of $W_i$ is $\sigma^2_W=\sigma^2_1+\sigma^2_2$.

Now we know that $W_i$ is drawn from some distribution (difference of two normals) with limited variance ($\sigma^2_1+\sigma^2_2$), therefore you can apply the weak law of large numbers:

Let $U_n=\frac{\frac{1}{n}\sum_{i=1}^nW_i-\mu_W}{\sqrt{\frac{\sigma^2_W}{n}}}$

By substituting $\sigma_W^2$ and $\mu_W$ the proof is complete:

$\frac{1}{n}\sum_iW_i = \frac{1}{n}\sum_i (X_i - Y_i)=\frac{1}{n}\sum_i X_i-\frac{1}{n}\sum_i Y_i=\bar{X} - \bar{Y}$

$U_n=\frac{(\bar{X} - \bar{Y})-(\mu_1-\mu_2)}{\sqrt{\frac{\sigma^2_1+\sigma^2_2}{n}}}$

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.